Research progress of immune checkpoint inhibitors in the treatment of glioblastoma - JIA Xiaorong; ZHANG Gong (Yixue xinzhi zazhi)
Glioblastoma (GBM) is the most invasive glioma in the central nervous system. Maximum surgical resection, chemotherapy and radiotherapy are currently the standard treatment for GBM. Due to the unique immune environment of the central nervous system, the application of immunotherapy in GBM is facing challenges. Immune checkpoint inhibitors (ICIs) is one of the main immunotherapy strategies for GBM. Clarifying the mechanism of ICIs in GBM and developing effective therapeutic targets are of great significance to prolong the survival of GBM patients. In the study, we summarize the research progress of blood-brain barrier, tumor microenvironment, immune cells, ICIs and their combination therapy in GBM to provide reference for GBM immunotherapy.